2021
DOI: 10.1177/2150135121999030
|View full text |Cite
|
Sign up to set email alerts
|

Current Management of Anomalous Aortic Origin of a Coronary Artery: A Pan-Canadian Survey

Abstract: Background: Anomalous aortic origin of a coronary artery (AAOCA) is a significant cause of sudden cardiac death (SCD) in children and adolescents. The natural history of AAOCA and the pathophysiology of AAOCA-related SCD are poorly understood. Therefore, the evaluation and management of AAOCA remain controversial. This survey-based study aims to report the current AAOCA management tendencies in Canada. Methods: We built a 23-question survey on AAOCA. Questions pertained to patient presentation, investigations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Surgery is recommended for all patients with AAOLCA in that guidance, leaving little need for risk strati cation. However, as was seen in the Canadian survey (24), an important minority of our respondents did not advocate surgical repair of AAOLCA in the absence of ischemia on stress imaging and the frequent recommendation for stress testing in AAOLCA may suggest that some cardiologists do see a role for risk strati cation in AAOLCA.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Surgery is recommended for all patients with AAOLCA in that guidance, leaving little need for risk strati cation. However, as was seen in the Canadian survey (24), an important minority of our respondents did not advocate surgical repair of AAOLCA in the absence of ischemia on stress imaging and the frequent recommendation for stress testing in AAOLCA may suggest that some cardiologists do see a role for risk strati cation in AAOLCA.…”
Section: Discussionmentioning
confidence: 65%
“…(23) Respondents to a survey of Canadian pediatric cardiologists and congenital heart surgeons published in 2021 were much less likely to recommend surgery for asymptomatic patients with AAOLCA and symptomatic patients with AAORCA than would be recommended in the 2017 AATS guidelines. (24)…”
Section: Introductionmentioning
confidence: 99%
“…[ 70 ] AAOCA is the second most common cause of SCD in children and adolescents, after hypertrophic cardiomyopathy (HCM). [ 71 ] High-risk features include intramural course, interarterial course, slit-like ostium, or acute angulation. [ 71 ].…”
Section: Congenital Anomaly Of the Coronary Arterymentioning
confidence: 99%
“…[ 71 ] High-risk features include intramural course, interarterial course, slit-like ostium, or acute angulation. [ 71 ]. A ‘scissor-like’ physiologic effect has been proposed in case of an interarterial AAOCA course, in which coronary artery compression between the great vessels occurs during times of high cardiac output, like exercise, leading to myocardial ischemia,[ 72 ] lethal ventricular arrhythmia or SCD.…”
Section: Congenital Anomaly Of the Coronary Arterymentioning
confidence: 99%
“…Anomalous aortic origin of the coronary artery (AAOCA) is a rare congenital cardiac abnormality that typically involves the left main coronary artery arising from the right sinus of Valsalva or the right coronary artery (RCA) arising from the left sinus [ 1 , 2 ]. In our case, coronary computed tomography (CT) showed that the RCA originated from the left sinus of Valsalva, indicating AAORCA.…”
Section: Introductionmentioning
confidence: 99%